Perbandingan Metode ARAS dan MOORA untuk Menentukan Santri Penerima Beasiswa Berprestasi - Yunika Rahmawati; Saifur Rohman Cholil (Teknik Informatika Universitas Pamulang, 2022)
The determination of outstanding scholarship recipients is usually only done through file selection, so it takes a long time and risks being less accurate in their determination, therefore research is carried out that aims to create a decision support system that can speed up the process of determining the recipient of the outstanding scholarship. The methods used are ARAS (Additive Ratio Assessment) and MOORA (Multi-Objective Optimization on the basis of Ratio Analysis). The selection of this method is able to filter the best alternatives based on weighting and this method is able to choose goals based on different criteria, namely benefits and costs. The result obtained from the ARAS method is a ranking calculation from the comparison of alternative utility functions with optimal utility function values, while the results obtained from the MOORA method are calculation rankings of maximum and minimum values. From these values produce alternatives that meet the criteria through calculations using the ARAS method and MOORA is selected as a scholarship recipient. Spearman Rank correlation test results from the ARAS method are 0.98 and the MOORA method is 0.97. The results of calculations using those done manually or using the system show the same results, meaning that the system can be used to determine the recipients of outstanding scholarships.